Oral History Program Interview: Esta Mae Lewis Rymal - Rymal, Esta Mae Lewis
Rymal was born in Cushing, Oklahoma in 1923. She and her family came out to Fresno and then Hanford, California in 1937 for a short time, moving to and from Oklahoma over the course of the next few years. She describes how the Corcoran cotton camp had similarities to The Grapes of Wrath, but her family did not live in the same manner. Rymal does not recall any discrimination, but her son finds the term "Okie" demeaning. She includes information on Oklahoma foods and farming.